Analysis of Risk Factors and Body Mass Index Against Degrees of Severity of Psoriasis Vulgaris - Lidjaja, Lifesia Natali; Muhammad Eko Irawanto; Nur Rachmat Mulianto; Arie Kusumawardani; Ivani; Vrenda Alia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Psoriasis vulgaris (PV) is a chronic inflammatory skin disease with a multifactorial etiology, including genetic, immunological, and environmental factors. Obesity, characterized by a high body mass index (BMI), has been increasingly recognized as a potential risk factor for PV and may influence its severity. This study aimed to analyze the relationship between various risk factors, particularly BMI, and the severity of PV. Methods: A cross-sectional study was conducted at a dermatology outpatient clinic of Dr. Moewardi Surakarta Hospital. Patients with a confirmed PV diagnosis were enrolled. Demographic data, medical history, lifestyle factors (smoking, alcohol consumption), and anthropometric measurements (height, weight, BMI) were collected. PV severity was assessed using the psoriasis area and severity index (PASI). Statistical analysis, including univariate and multivariate logistic regression, was performed to identify associations between risk factors and PV severity. Results: The study included 200 PV patients with a mean age of 45.2 years (SD = 12.8) and a male predominance (58%). The mean PASI score was 12.4 (SD = 8.6), indicating a wide range of disease severity. Multivariate analysis revealed that obesity (BMI ≥ 30 kg/m2) was significantly associated with increased PV severity (odds ratio [OR] = 2.8, 95% confidence interval [CI] = 1.5-5.2, p = 0.001). Smoking (OR = 1.9, 95% CI = 1.1-3.3, p = 0.02) and a family history of psoriasis (OR = 2.3, 95% CI = 1.3-4.1, p = 0.004) were also identified as independent risk factors for higher PASI scores. Alcohol consumption showed a borderline association with increased severity (OR = 1.6, 95% CI = 1.0-2.6, p = 0.05). Conclusion: Obesity, smoking, and a family history of psoriasis are significant risk factors for increased PV severity. These findings underscore the importance of addressing modifiable risk factors, such as weight management and smoking cessation, in the holistic management of PV. Further research is warranted to elucidate the underlying mechanisms linking these risk factors to PV severity and to develop targeted interventions to improve patient outcomes.